2009
DOI: 10.1111/j.1365-2567.2008.02949.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathways regulating lipopolysaccharide‐induced neutrophil survival revealed by lentiviral transduction of primary human neutrophils

Abstract: Summary Human neutrophils express Toll‐like receptor 4 (TLR4) at low levels, and the role of this receptor in neutrophil responses to microbial stimuli has been questioned. Genetic manipulation of these cells to enable the study of the role of proteins such as TLR4 in their function is challenging. Here, we show that primary human neutrophils rapidly express novel proteins such as enhanced green fluorescent protein (eGFP) after transduction with lentivirus. Stimulation of transduced neutrophils with lipopolysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Prolongation of neutrophil survival by LPS stimuli is mediated by Toll-like receptor 4-MyD88 pathway, which activated nuclear factor κB. (16) Mitogen-activated protein kinase (MAPK) also plays critical roles for neutrophil survival. In the presence of LPS, the signals generated via activated extracellular signal-regulated protein kinases (ERK) may inhibit the regulation of neutrophil apoptosis by p38MAPK, resulting delayed neutrophil apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Prolongation of neutrophil survival by LPS stimuli is mediated by Toll-like receptor 4-MyD88 pathway, which activated nuclear factor κB. (16) Mitogen-activated protein kinase (MAPK) also plays critical roles for neutrophil survival. In the presence of LPS, the signals generated via activated extracellular signal-regulated protein kinases (ERK) may inhibit the regulation of neutrophil apoptosis by p38MAPK, resulting delayed neutrophil apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies previously demonstrated an association of the TLR4 gene with enhanced neutrophil survival by inhibiting neutrophil apoptosis. 9,11-13 Dick et al 10 showed that neutrophil survival is inhibited when neutrophils are transduced with a lentivirus encoding a dominant-negative TLR4 protein, and that neutrophils can be genetically manipulated to enhance or inhibit survival. OR is calculated by logistic regression (95% CI) in their best-fitting model (D ¼ minor allele is dominant and R ¼ minor allele is recessive).…”
Section: Discussionmentioning
confidence: 99%
“…A candidate gene that might be associated with the risk of developing chemotherapy-induced neutropenia is Toll-like receptor 4 (TLR4), as TLR4 has been shown to have a role in inhibition of neutrophil apoptosis, and extension of the functional lifespan of neutrophils during stimulation with lipopolysaccharide. [9][10][11][12][13] TLR4 is 1 of 11 known mammalian Toll-like membrane receptors that have a key role in innate immunity by detecting and eliminating invading pathogens. Expression of TLR4 has been detected on neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…Except for intracellular TLR3, human neutrophils express all other TLRs, highlighting their importance in the induction of an immune response [121]. TLR stimulation on neutrophils contributes to a prolonged lifespan of this otherwise short-lived cell population [122]. It also modulates cell surface receptor expression and initiates degranulation processes as well as ROS production and phagocytosis - all of which add to their potent microbicidal and proinflammatory effects [123].…”
Section: Tlr Responsive Cell Types In Wound Healingmentioning
confidence: 99%